DYNAMIC ANALYSIS OF NON-PNEUMATIC TIRES WITH HONEYCOMB SPOKES ON SPEED BUMPS - Sriwijaya, Rachmat; Ghiffari , Fakhri; Ra’if , Zahran; Wijaya, Burhani (Jurnal Rekayasa Mesin, 2024)
The Non-Pneumatic Tire (NPT) has rapidly developed as an alternative to the Pneumatic Tire since it was created by Michelin in 2005. This research aims to investigate the influence of load and speed on the stress experienced by honeycomb-structured spokes of NPT tires when passing over speed bumps and the behavior of stress distribution in honeycomb spokes. Using the ANSYS Explicit Dynamics module, the chosen simulation method is the finite element method with transient dynamics. Several simulations were conducted by varying the load and initial speed of the NPT. The results of this study indicate that the higher the initial speed of the NPT, the higher the stress experienced by the spokes. Conversely, for all examined speeds, load variations do not significantly impact the stress level in the spokes. Further study on the behavior of NPT tires on inclined roads was also conducted.